Implementation Of The Talent Management Program at PT Jet Teknologi Express (JnT Express) at Cilegon Branch - Khoi, Boidatul; Nopiani; Digdowiseiso , Kumba (CV ODIS, 2024)
The aim of this research is to identify and analyze planning, development, management and how to maintain talent management at PT Jet Tekonologi Express. This research was carried out at PT Jet Tekonologi Express Cilegon Branch or known as JNT. The method used is a qualitative method with interviews with high-ranking members of PT Jet Tekonologi Express. The competitiveness of Indonesia's human resources is still lower than Singapore, Malaysia and Thailand. This requires developing the skills of Indonesian human resources and encouraging companies to face the talent war that is occurring. Management Trainee is one of the strategies implemented in various companies. The results of this research show that the most influential talent management factor is skills, the most dominant talent management actors are leaders & top management and human capital, the most important goal is to produce potential company executives, and the most influential alternative strategy is attracting